Indole based Tubulin Polymerization Inhibitors: An Update on Recent Developments - Sunil, Dhanya; R. Kamath, Pooja (Mini Reviews in Medicinal Chemistry, 2016)
The exploration of cancer microenvironment and its physiology have exposed a number of potential molecular targets for selective therapeutic intervention by anti-cancer agents. Microtubules are basic cell components formed by polymerization of αβ heterodimers which play a pivotal role in cellular functions as well as cell division. Drugs that can control the microtubule assembly either by hindering tubulin polymerization or by obstructing microtubule disassembly are of great importance in anti-cancer therapy. Diverse classes of naturally occurring as well as synthetic and semi-synthetic compounds with an indole nucleus induce microtubule polymerization and depolymerization and thereby change tubulin dynamics. Rapid development of several novel tubulin polymerization inhibitors has been observed over the past few years and some of them have associated vascular disrupting properties too. The present review starts with the structure, function and importance of microtubules in a eukaryotic cell. The well characterized tubulin binding domains and the corresponding inhibitors including their mechanism of action is also a part of this article. The report mainly focuses on the brief synthetic methodology with the relevant SAR studies of different indole derived molecules that have been reported in the past few years as potential inhibitors of tubulin polymerization is discussed. This review will provide the up-to-date evidence-base for synthetic chemists as well as biologists to design and synthesize new active molecules to inhibit tubulin polymerization.
Keywords: Indole